Changes of internal structure of movement in speed skating - Gołaś, Artur; Krzysztofik, Michał; Drozd, Miłosz; Roczniok, Robert; Trebert, Marta; Zając, Tomasz; Maszczyk, Adam (Akademia Wychowania Fizycznego w Poznaniu)
Speed skating is a competitive form of ice skating in which the athletes race each other at distances from 500 to 10000 m. In speed skating the main components of specific fitness include acceleration, anaerobic sprint ability and explosive power of the lower extremities. A specific starting pattern in speed skating affects the relationships between strength of individual muscle groups. The main aim of this study was to analyse the pattern of internal structure of specific speed skating movements depending on their velocity – % PSE. The study examined six female athletes from the Polish National Speed Skating Team. The results of muscle activity index (4/7 and 4/10 PES mean) revealed statistically significant differences for the GM (Z=2.36;p=0.017), A (Z=2.02; p=0.04) and BF (Z=2.20; p=0.027) muscles respectively. The same analysis was performed for differences between peak activities at intensities of 4/7 PES and 4/10 PES. The results revealed statistically significant differences for the TFL (Z=2.52; p=0.011) and A (Z=2.20; p=0.027) and BF (Z=2.36;p=0.017) muscles. The results obtained in this study show that the more effective use of Gluteus Medius (GM), Adductor (A), Biceps Femoris (BF) and Tensor Fasciae Latae (TFL) muscles substantially improves starting speed in speed skating
Keywords: slide board; muscle activity; movement pattern